Global, regional, and national burden of four major neurological diseases in women from 1990 to 2021 - Guo, Xiaofang; Liu, Xinghua; Lin, Jian; Huang, Zitian; Lin, Sixing; Zhang, Mengfan; Xu, Zihan; Lin, Xingdong (Frontiers in Public Health, 2025)
BackgroundThe burden of neurological diseases in women is underestimated. This study aimed to estimate the pattern and trend of four major nervous system diseases in women.MethodsUtilizing data from the GBD Study 2021 on the incidence and disability-adjusted life-years (DALYs) of Alzheimer’s disease (AD) and other dementias, Parkinson’s disease, multiple sclerosis, and idiopathic epilepsy in women from 1990 to 2021. We estimated trends by age and socio-demographic index (SDI), globally, regionally, and nationally, using Estimated annual percentage changes (EAPC), Spearman correlation analysis and projected future trends with the Bayesian age-period-cohort (BAPC) model.ResultsIn 2021, an estimated 6191564.2, 572999.9, 1536118.7, and 39191.7 new cases of female AD and other dementias, Parkinson’s disease, multiple sclerosis, and idiopathic epilepsy were reported globally, with a significant increase in age-standardized incidence rate (ASIR) from 1990 to 2021. Contrary, the age-standardized DALY rate (ASDR) decreased in idiopathic epilepsy and multiple sclerosis. AD and other dementias and Parkinson’s disease were prevalent among women worldwide, followed by idiopathic epilepsy and multiple sclerosis, with regional and country disparities. There are also difference of patterns among age and SDI. The BAPC model projects that by 2050, the ASIR of the four major neurological disorders will continue to increase.ConclusionThe burden of major neurological diseases in women is a serious global health challenge. Given the regional disparities and varying age patterns in incidence and DALYs, there is an urgent need for tailored prevention and healthcare approaches to mitigate the burden worldwide.